Ein Lehrreicher Vergleich für Jeden Fachmann - P. F. Dujardin & Co. (1914)
Advertisement from P. F. Dujardin & C depicting Bunsen burners and a Meker burner.
Keywords: Bunsen burner; Gas-burners; Illustrated works; Scientific apparatus and instruments; P. F. Dujardin & Co.